The effect of build orientation and surface modification on mechanical properties of high speed sintered parts. (4th September 2015) - Ellis, Adam; Brown, Ryan; Hopkinson, Neil
Abstract: High speed sintering is a novel additive manufacturing technology that uses inkjet printing and infra-red energy to selectively sinter polymeric powder. The research presented here investigates the effect of build orientation on dimensional accuracy, density, mechanical properties and surface roughness of high speed sintered parts. Tensile specimens were built through seven different angles between and including the XY (horizontal) and ZY (vertical) planes and analysed. The effect of the PUSh™ process was also investigated across this range of build orientations. The results show that build orientation does infuence the properties of the parts. A number of mechanical properties showed a relationship with build orientation. Density was seen to decrease as the angle increased from XY towards ZY . This increase in angle was shown to increase surface roughness while ultimate tensile strength and elongation at break decreased. At all build orientations, the PUSh™ process significantly reduces surface roughness, mildly increases part density and had a small effect on ultimate tensile strength whilst showing a small but consistent increase in elongation at break.